PRODUCTION SUSTAINABILITY OF BATIK CIPRAT DURING THE COVID-19 PANDEMIC IN SPECIAL SCHOOL JEPON BLORA REGENCY - Eva Hertnacahyani Herrapratanti; Hendri Suryanto; Helmi Gunawan; Mochamat Slamet Riyadi (International Journal of Engagement and Empowerment, 2022)
SLB N Jepon-Blora is one of the special schools that accommodates all types of disabilities by providing Batik Ciprat skills. Batik Ciprat's skills are carried out at school. Still, during the Covid-19 pandemic, students learned from home so that the production of Batik Ciprat was temporarily stopped, even though there was still a demand for Batik Ciprat from consumers. The tools used by SLB N Jepon-Blora's students in producing Batik Ciprat are straightforward. “Gawangan” means spreading cloth made of paralon pipes arranged like a table frame. These hurdles are inefficient, easily damaged, require ample space in storage. The STT Ronggolawe Cepu made a portable frame from stainless steel, which is designed to be folded so that it is practical and does not require ample space in terms of storage. This program aims to see the sustainability of the STT Ronggolawe Cepu team's activities at SLB N Jepon-Blora. The program's conclusions are as follows: 1) the tools submitted by the STT Ronggolawe Cepu Team still exist and are still being used in the Batik Ciprat production process before the Covid-19 pandemic. 2) the sustainability program has encountered obstacles from external factors, such as the natural conditions of the Covid-19 pandemic, causing the production of Batik Ciprat SLB N Jepon-Blora to be temporarily suspended.